Introduction to Climate Action Task Force 2023 Plenary Lecture and Forum - Martin, Patricia M.; Nevins, Joseph (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This special issue emerges out of the plenary lecture sponsored by the American Association of Geographers (AAG) Climate Action Task Force at the AAG Annual Meeting in April 2023. The lecture was the opening session of a “node” based in Montreal. The issue comprises revised versions of the original lecture and the comments offered by three respondents, as well as an essay inspired by the node. All the pieces consider academic (in)mobility, the need to transform institutional practices and how to do so in a way that advances social justice rather than reproducing unjust hierarchies and exclusions.